Successful Salvage of Pedicled Latissimus Dorsi Flap after Venous Thrombosis by Selective Thrombolytic Therapy - Kosuke Maitani, MD; Koichi Tomita, MD, PhD; Hiroki Tashima, MD; Michiko Nomori, MD; Mifue Taminato, MD; Tateki Kubo, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2020)
Summary:. While the use of free flaps has become routine and is associated with a low complication rate, pedicled flaps remain a solid reconstructive option in various clinical situations. Pedicled flaps provide a reliable vascular supply and involve a simple surgical procedure. Although the procedure is advantageous from the standpoint of a low rate of flap ischemia, thrombosis, and total flap loss, these complications are still occasionally observed due to intraoperative pedicle injury, postoperative torsion, or compression. Here we report on a case of severe venous thrombosis in a pedicled latissimus dorsi (LD) flap used for breast reconstruction. The patient was a 52-year-old woman who underwent mastectomy and immediate breast reconstruction with a LD flap for left breast cancer. Postoperatively, the color of the skin paddle became dark blue over time. Emergent surgical exploration revealed kinking and narrowing of the thoracodorsal vessels and extensive venous thrombi. The kinked pedicles were repaired and selective thrombolytic therapy was performed. A thrombolytic agent was administered through the serratus anterior branch of the thoracodorsal artery in retrograde fashion while the thoracodorsal vessels were clamped just cephalad to the bifurcation. This allowed for draining of the thrombolytic agent and thrombi through the serratus anterior branch of the thoracodorsal vein without flowing into the systemic circulation. To the best of our knowledge, this is the first report of selective thrombolysis using a pedicle branch to treat venous thrombosis in a pedicled flap. If major vascular branches are available in a pedicled flap, selective thrombolytic therapy may be possible without disconnecting the pedicle, as in the present case.